The Lean Government Development on Public Services over Publishing Letter Police Record at State Police Office, Indonesian Republic - Jayanti Mayasari Simamora; Tantri Yanuar Rahmat Syah (Penerbit Kemala Indonesia, 2020)
Lean is part of a growing management trend and designed to reduce administration costs also operating efficiency at companies or government sectors. Lean has a consideration concept to implement properly in public service. Thus, in this study, we analyze Lean Government in the public service sector for issuing Surat Keterangan Catatan Kepolisian (SKCK) in Indonesian police. Here, we use qualitative methods to obtained data observation based on field shots, documents analysis, and notes or reports. The results showed that Lean Six Sigma be able to applied with LCM to improving the SKCK request service process by reducing the total time of service completion both from the service provider side, from 185 minutes to 30 minutes and from the service user side from 171 minutes to 40 minutes. Therefore, the percentage of value-added also increased from the service provider side from 36.8% to 40% and on the service user side the value-added percentage increased from 21.6% to 32.5%.